Estudo comparativo in vitro da resistência ao cisalhamento de braquetes colados com resinas restauradoras e ortodôntica - Isber, Hassan (2009)
The aim of this study is to assess the shear bond strenght of brackets bonded with different restorative resins and compare them to the resistance provided by a specific orthodontic bonding system. Seventy human bicuspids teeth were used, divided among five different groups with 14 teeth in each one of them. While the control group uses a specific orthodontic bonding resin (Transbond XT), the other four groups use restorative resins (Charisma, Tetric Ceram, TPH Spectrum and Z100). Seven days after bonding the brackets to the samples, they were submitted to the strengths of shearing by pressure by a universal testing machine. The data collected was evaluated using the ANOVA and, when a difference was identified, the Tukey test was applied. The significance level used was 5 %. After the shearing tests, the following average results were: Group 1 (Charisma) 14,98 MPa; Group 2 (Tetric Ceram) 15,16 MPa; Group 3 (TPH) 17,70 MPa; Group 4 (Z100) 13,91 MPa and Group 5 – control group (Transbond XT) 17,15 MPa. No statistical significant difference was found between groups, which mean that any of the tested resins can be, safely, recommended for bonding orthodontics brackets.